THE INFLUENCE OF SERVICE QUALITY AND INTERNET PRODUCT PRICES ON TELKOMSEL PREPAID CUSTOMER SATISFACTION - Febrian A, Muh Fadhli; Prastiwi, Dian; Pakan Tangdilinting, Efrain Chandra; Yogi, Muhammad; Santoso, Budi; Panada, Yuhelti Marran (Universitas Ichsan Sidenreng Rappang, 2023)
This research aims to determine the simultaneous and partial influence of service quality and internet product prices on Telkomsel prepaid consumer satisfaction (Case Study of Students at the Faculty of Economics and Business, Andi Djemma Palopo University). The population and sample in this study were 35 samples with an incidental sampling technique, namely a sampling ability technique based on chance. Data collection techniques include questionnaires or questionnaires. Data analysis techniques use validity tests, reliability tests and multiple linear regression tests, with the help of SPSS version 21 for Windows. Based on data processing using multiple linear regression analysis as described in the results and discussion, it can be concluded that simultaneously the variables of service quality and price have a significant effect on consumer satisfaction. The service quality variable has a significant effect on consumer satisfaction. The price variable has a significant effect on consumer satisfaction.